Evaluation of mechanical properties of hybrid Al7009 nanocomposite. Issue 2 (17th January 2021) - Senthilkumar, P.; Manimaran, R.; Krishna Reddy, Y.
ABSTRACT: Hybrid nanocomposites are prepared by Al7009 aluminum alloy as base material, graphite and nano magnesium oxide (MgO) as reinforcements. Stir casting processes are used for preparation of hybrid nanocomposite, the percentage of graphite is fixed at 1 wt.% and nano magnesium oxide is varied for 1%, 2%, and 3% by weight and the specimens are named as A (pure), B (1% graphite and 1% MgO), C (1% graphite and 2% MgO), and D (1% graphite and 3% MgO). Evaluation of mechanical properties such as compressive strength, hardness, density, and impact strength behavior of hybrid Al7009 nano aluminum composites are analyzed. From the experimental results, the compressive strength and hardness of hybrid nanocomposite increases up to 2% wt of nano MgO particles and then the value decreases for 3% wt of nano MgO particles. Density increases from the specimens A to C with an increase in percentage of reinforcement in the matrix phase and then it decreases for specimen D. With respect to toughness highest value of 4.4 Jis obtained for sample D and the increase in percentage was 62.9 when compared to sample A, it was 37.5% when compared to specimen B and 12.8% when compared to specimen C.